Evaluating The Effectiveness Of Diverse Preventive Strategies For Sports Injuries: A Systematic Review Of Randomized Controlled Trials (The Review of Diabetic Studies, 2025)
Introduction: Sports have important implications for population health. Therefore, it is challenging to reduce and prevent these injuries. This systematic review aims to assess, update, and summarize studies discussing the different prevention strategies for sports injuries and highlighting their effects and implications for different populations. Methods: A systematic search identified randomized controlled trials (RCTs) published up to June 2024 using PubMed, Medline, OVID, Scopus, and Cochrane Central Register of Controlled Trials. Inclusion criteria were studies examining the effects of preventive interventions on sports injuries among adolescents and adults. Thirteen studies met the criteria, covering interventions such as neuromuscular training (NMT), balance programs, FIFA 11+, lace-up ankle braces, perturbation training, laser therapy, mindfulness, and fascial manipulation. Results: The interventions demonstrated varying levels of effectiveness. NMT programs reduced lower extremity injuries, including a 32% reduction in non-contact injuries (95% CI: 0.51-0.93). Lace-up ankle braces halved the risk of ankle sprains (HR=0.39, 95% CI: 0.24-0.65, p